(untitled) (International Journal of Engineering and Computer Science, 2015)
Authentication is considered as a significance element of security to verify user’s identity. There are many authentication schemes that depend on user name /password ,but they are considered weak techniques of user authentication because they are prone to dictionary attack and man in middle attack , etc. A more secure scheme is 2 factor authentication that does not only verify the user name /password pair, but also needs a second factor such as a token device, biometric. This paper proposes the comparative study of different two and three factor authentication techniques, that can withstand common security attacks as well and has good performance of user authentication.